The Contribution of English Gossip Magazine on Students’ Enthusiasm in Speaking Ability - Ismail Ismail (Universitas Muhammadiyah Enrekang, 2017)
This current study sought to reveal the impacts of corpus-based activities on verb-noun collocation learning in EFL classes. This study was carried out on two groups – experimental and control groups- each of which consists of 15 students. The students were preparatory class students at School of English Department, STKIP Muhammadiyah Enrekang. Before the treatment, a pretest was administered to both groups. The results of the pretest demonstrated that there was not significant difference between the control and the experimental group. Throughout the study, the experimental group was taught speaking through English Gossip Magazine materials taken from webzines, and the control group was taught through a conventional method. The results demonstrated that there is a statistically significant difference between experimental and control group in terms of the type of treatment, which signifies that English Gossip Magazine as a resource of learning material activities has a significant contribute on speaking development in EFL classes.